2018
DOI: 10.3390/nu10070909
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Locally Produced, Fish-Based Food Product on Weight Gain among Cambodian Children in the Treatment of Acute Malnutrition: A Randomized Controlled Trial

Abstract: Cambodia continues to have a high prevalence of acute malnutrition. Low acceptability has been found for standard ready-to-use-therapeutic-food (RUTF) products. Therefore, NumTrey, a locally-produced fish-based RUTF, was developed. The objective was to evaluate the effectiveness of NumTrey compared to an imported milk-based RUTF for weight gain among children aged 6–59 months in the home-treatment for acute malnutrition. Effectiveness was tested in a single-blinded randomized controlled trial with weight gain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(76 citation statements)
references
References 49 publications
(66 reference statements)
4
62
0
10
Order By: Relevance
“…Linear growth observed in the trial (2.6 mm/week with reduced dose and 2.8 mm/week with standard dose) is in line with other CMAM studies [5,6,9,10,16,19,38] and with the 2.8 mm/week growth rates expected in healthy 13-month-old children [39]. However, the reduced dose slowed down the linear growth of children by 0.2 mm/week (95% CI 0.04 to 0.4; p = 0.015).…”
Section: Discussionsupporting
confidence: 90%
“…Linear growth observed in the trial (2.6 mm/week with reduced dose and 2.8 mm/week with standard dose) is in line with other CMAM studies [5,6,9,10,16,19,38] and with the 2.8 mm/week growth rates expected in healthy 13-month-old children [39]. However, the reduced dose slowed down the linear growth of children by 0.2 mm/week (95% CI 0.04 to 0.4; p = 0.015).…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that the locally-produced fish-based RUTF performed as well as BP-100™ and is a potential alternative to the latter for SAM treatment in Cambodia. Details on the RUTF effectiveness trial are reported elsewhere [46].…”
Section: Methodsmentioning
confidence: 99%
“…Replacement of lost fish with other food sources is beyond the scope of this analysis, but is an important future direction for research. Some groups have even demonstrated, through randomized control trials, the importance of local fish food products in improving Cambodian nutrition (Sigh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%